The fourth dimension: why time is of the essence in sacramental theology - Wright, Claire Louise (The Australasian Catholic record, 2017)
If the sacraments are, as Louis-Marie Chauvet argues, the major symbolic expressions of "the body as the point where God writes God's self in us", few concepts could be more central to sacramental theology than time, the medium in which human, ecclesial, cultural and cosmic "bodies" have their being and expression. Christian narratives, traditions and rituals are founded in history and the shared memory of culture. As Miroslav Volf notes, the "sacred memory" of the death and resurrection of Christ defines the identity of Christians as "the pulsating heart that energizes and directs their actions (in the present) and forms their hopes (for the future)". Indeed, all human experience, identity and meaning-making are mediated by an awareness of time, the flow and relativity of chronos and the moment(ousness) of kairos. As Chauvet puts it, the "sensible mediation" of history (together with language, body and desire) comprises 'the very milieu within which human beings attain their truth and thus correspond to the Truth which calls them".